The Meaning of Consuming Halal Products According to Muslim Millennial Generation in Realizing Of Maqasid Sharia “Maslahah” - Mursal - Mursal; Muhammad Fauzi; Alan Rakhmat Putra; Al Mahdi (Prodi Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2025)
Purpose – This study aims to explore the meaning of the concept of halal product consumption by millennial Muslims as part of their identity and lifestyle. The main focus is to understand how millennial Muslims interpret halal product consumption not only as a religious rule but also as a symbol of quality, and social identity. Method – The research method used is quantitative and qualitative, qualitative data collection using in-depth interviews with 10 informants and supported by survey data from 70 millennial Muslim generation respondents with purposive sample techniques. The respondents came from students of the Sharia Faculty of IAIN Kerinci, Study Program